2022
DOI: 10.3390/gastroent13010010
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation Induces Tuft Cell Hyperplasia and Myenteric Neuronal Loss in the Absence of Dietary Fiber in a Mouse Model of Pelvic Radiotherapy

Abstract: Pelvic radiotherapy is associated with chronic intestinal dysfunction. Dietary approaches, such as fiber enrichment during and after pelvic radiotherapy, have been suggested to prevent or reduce dysfunctions. In the present paper, we aimed to investigate whether a diet rich in fermentable fiber could have a positive effect on radiation-induced intestinal damage, especially focusing on tuft cells and enteric neurons. Male C57BL/6 mice were fed either a purified non-fiber diet or the same purified diet with 5% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…These cells communicate with luminal bacteria and interact with the afferent and efferent nerve terminals in the lamina propria by activated chemosensory receptors [95]. Though ECC comprises only 1% of intestinal epithelial cells, they produce and release 90% of the body's 5-HT [96,97]. Chen et al demonstrated that under environmental stress, epithelial cells released interleukin-33, which binds to suppression of tumorigenicity 2 receptors on ECC.…”
Section: Enteroendocrine Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…These cells communicate with luminal bacteria and interact with the afferent and efferent nerve terminals in the lamina propria by activated chemosensory receptors [95]. Though ECC comprises only 1% of intestinal epithelial cells, they produce and release 90% of the body's 5-HT [96,97]. Chen et al demonstrated that under environmental stress, epithelial cells released interleukin-33, which binds to suppression of tumorigenicity 2 receptors on ECC.…”
Section: Enteroendocrine Cellsmentioning
confidence: 99%
“…This suggests the potential of a bidirectional communication with the ENS (Figure 3). Tuft cells and submucosal and myenteric neurons express the SCFA receptor (FFAR3, free fatty acid receptor 3), the stimulation of which may modulate neuronal activity [97]. Both tuft cells and myenteric excitatory neurons express ChAT [97], and reduced ChAT signaling from enteric neurons appears to provoke an increase in tuft cells to maintain cholinergic homeostasis [102].…”
Section: Tuft Cellsmentioning
confidence: 99%
See 1 more Smart Citation